2019
DOI: 10.1088/1361-6528/ab3d1c
|View full text |Cite
|
Sign up to set email alerts
|

Au nanoclusters/porous silica particles nanocomposites as fluorescence enhanced sensors for sensing and mapping of copper(II) in cells

Abstract: In this work, we first report Au nanoclusters/porous silica particles nanocomposites as fluorescence enhanced sensors for selective and sensitive detection of Cu (II). As red-emitting GSH-protected Au nanoclusters (Au NCs) were self-assemble into porous silica particles (PSPs) after ultrasonic treatment. As a result, the Au NCs can be immobilized in the nano-channels of PSPs, which leads to the observation of an immobilized induced emission enhancement phenomenon. The photoluminscence (PL) intensity of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…As among the most produced engineered nanomaterials, silica nanoparticles (NPs) were extensively used in various traditional industrial manufacturing products including plastics, rubbers, ceramics, pigments, coatings, and cosmetics. Recently, due to their high surface area and better biodegradability, silica NPs were applied in many biomedical fields, for example, diagnosis, bone regeneration scaffolds, , drug delivery carriers, , and cancer therapies. With increasing industrial production and applications, the exposure of silica NPs gradually increases via dietary intake, skin contact, respiration, and systematic administration . Recently, studies demonstrated that the exposure of silica NPs could cause significant in vitro , and in vivo toxicities. , …”
Section: Introductionmentioning
confidence: 99%
“…As among the most produced engineered nanomaterials, silica nanoparticles (NPs) were extensively used in various traditional industrial manufacturing products including plastics, rubbers, ceramics, pigments, coatings, and cosmetics. Recently, due to their high surface area and better biodegradability, silica NPs were applied in many biomedical fields, for example, diagnosis, bone regeneration scaffolds, , drug delivery carriers, , and cancer therapies. With increasing industrial production and applications, the exposure of silica NPs gradually increases via dietary intake, skin contact, respiration, and systematic administration . Recently, studies demonstrated that the exposure of silica NPs could cause significant in vitro , and in vivo toxicities. , …”
Section: Introductionmentioning
confidence: 99%
“…From this works, it can be seen that the addition of different polymeric materials resulted in different assembly processes at the same power. The ultrasound field enhanced the emulsification of non-ionic polymers [ 65 , 66 , 67 ] but also strengthens the binding between Au and Ag clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The relative fluorescence intensity of I 565 (the excitation/emission slit width was set at 5 nm, separately) of the CPDs and the concentration of N 2 H 4 ·H 2 O were also observed. 35 The fluorescence spectra of N 2 H 4 ·H 2 O, H 2 O, CH 3 OH, CHCl 3 , C 4 H 8 O 2 , C 6 H 15 NO 3 , CH 3 NO, CH 3 COCH 3 , C 6 H 14 , C 3 H 8 O, C 2 H 5 OH, AA to CPDs were tested under the same conditions. Compared with other interfering solvents, the CPDs had better selectivity for N 2 H 4 ·H 2 O.…”
Section: Methodsmentioning
confidence: 99%